PATIENT SATISFACTION QUALITY DESIGN BASED ON MINAHASA CULTURE AT RSUD Dr. SAM RATULANGI TONDANO PHENOMENOLOGY STUDY - Prisylia Meggy Wuisang; Blacius Dedi; Susi Nurhayati (Universitas Karya Husada Semarang, 2025)
Background. Minahasan culture has an important role in shaping community attitudes and behavior, including in health services, with cultural values If All Children Tumou Too, has principles that are very relevant in improving the quality of hospital services. This design aims to integrate local Minahasan wisdom into the hospital service system to increase patient satisfaction. The aim of this research is to determine the quality of patient satisfaction based on Minahasa culture at RSUD Dr. Sam Ratulangi Tondano Method. The research design used was qualitative phenomenological. The source of informants or participants in this study were 10 people consisting of patients or families of patients who were undergoing treatment in the surgical room at RSUD Dr. Sam Ratulangi Tondano. Primary data was obtained through in-depth interviews using interview guides conducted with informants. Data analysis in this research uses content analysis Results. The research results showed that there were 5 themes that emerged, namely: Responsiveness in accordance with Minahasa culture, Malinga-lingaan (listen to each other), Empathy, that is Mangenang-genangan (feeling what the patient feels, praying for each other, visiting). Tangible, that is Maesa-esa’an, (must be united), Maesa-esa’an (remind each other), Reliability that is Matombo-tombolan (support each other) and Assurances that is Mapalus, (help and please help). In providing health services, especially at RSUD Dr. Sam Ratulangi Tondano Minahasan culture continues to be preserved, especially in context ma-saali (service), where a nurse provides good service to patients, both in terms of appearance and friendliness. Conclusion. Aspects of Minahasan culture applied at RSUD Dr. Sam Ratulangi Tondano, namely Malinga-lingaan (listen to each other), Maleo-leosan (attitudes and behavior that love each other), Maesa-esa’an, (must be united), Mangenang-genangan (remind each other), Matombo-tombolan (support each other) and Mapalus, help each other and help each other. Suggestion. For the hospital to make signboards to rooms or corridors, providing announcements using language Tolour or Tondano language, and wearing work clothes/uniforms using local batik (batik bentenan) and for nurses and medical personnel to provide hospital services with Minahasan cultural dimensions, magenang-genangan, masawang-sawangan, matombo-tombolan, malinga-lingaan dan maleo-leosan